Yamanaka Factors in the Budding Tunicate Botryllus schlosseri Show a Shared Spatio-Temporal Expression Pattern in Chordates - Vanni, Virginia; Salonna, Marika; Gasparini, Fabio; Martini, Margherita; Anselmi, Chiara; Gissi, Carmela; Manni, Lucia (Frontiers in Cell and Developmental Biology, 2022)
In vertebrates, the four transcription factors Sox2, c-Myc, Pou5f1 and Klf4 are normally co-expressed in embryonic stem cells and play roles in pluripotency, self-renewal, and maintenance of the undifferentiated state in adult cells. The in vitro forced co-expression of these factors, named Yamanaka factors (YFs), has been demonstrated to be sufficient to induce pluripotency in human or mouse fibroblasts. Botryllus schlosseri is a colonial tunicate that undergoes continuous stem cell-mediated asexual development, providing a valuable model system for the study of pluripotency in the closest living relatives of vertebrates. In this study, we identified the B. schlosseri orthologs of the human Sox2 and c-Myc genes, as well as the putative ancestors of the vertebrate-specific Pou5f1 gene, through an in-depth evolutionary analysis of the YF gene family in tunicates and other deuterostomes. Then, we studied the expression of these genes during the asexual cycle of B. schlosseri using in situ hybridization in order to investigate their possible involvement in the development and in the maintenance of pluripotency. Our results show patterns of expression consistent with the reported function of these genes in invertebrates and vertebrates. Moreover, the expression of Myc, SoxB1 and Pou3 was detected in candidate stem cells residing in their niches, while Pou2 was found expressed exclusively in the immature previtellogenic oocytes, both in gonads and circulating in the colonial vascular system. Our data suggest that Myc, SoxB1 and Pou3 may play a role in stemness and differentiation even in this colonial ascidian